2016
DOI: 10.1097/xce.0000000000000075
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of frailty and sarcopaenia in diabetes mellitus: description of inter-relationships and clinical importance

Abstract: Diabetes mellitus is a highly prevalent chronic disease, with an associated heavy personal and public health burden of disability, morbidity and mortality. The focus of care for older patients with diabetes is prevention of functional decline, with early intervention rather than attempting to recover function later. Diabetes doubles the risk of frailty. An important contributor towards physical frailty is sarcopaenia, which manifests as an age-related loss of skeletal muscle volume and power. Frailty is not an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
(79 reference statements)
1
2
0
Order By: Relevance
“…First, type 2 diabetes was a significant determinant of physical frailty, consistent in both women and men. There is a strong association between frailty and diabetes in general, 43 and our findings demonstrate that this association persists in HF. Second, we found that sex moderates the relationship between having a comorbidity of stage 3 chronic kidney disease and physical frailty in HF.…”
Section: Discussionsupporting
confidence: 63%
“…First, type 2 diabetes was a significant determinant of physical frailty, consistent in both women and men. There is a strong association between frailty and diabetes in general, 43 and our findings demonstrate that this association persists in HF. Second, we found that sex moderates the relationship between having a comorbidity of stage 3 chronic kidney disease and physical frailty in HF.…”
Section: Discussionsupporting
confidence: 63%
“…It is likely that this trend would remain the same since physical activity decreases with age. Diabetes combined with physical inactivity accelerates muscle loss in older adults, and the most effective exercise intervention for older adults with diabetes is a combination of resistance and endurance training [33, 34]. For frail, older adults with diabetes and severe functional decline, a multicomponent exercise program is recommended which addresses gait and balance, as well as endurance and power training to counteract functional decline and reduce incidence of falls [33, 35].…”
Section: Exercise and Frailtymentioning
confidence: 99%
“…For older adults with frailty and diabetes, specific guidelines on frequency of exercise performance, repetitions, and progression of intensity for both resistance and endurance training have been proposed [34, 37]. However, attrition can be high and the proportion of older adults that stay engaged in recommended exercise programs has not been determined.…”
Section: Exercise and Frailtymentioning
confidence: 99%